The importance of pumpkin (Cucurbita L) in medicine and folk medicine - Orazimbetov Edilbek Kaypbekovich (Zien Journals, 2025)
Pumpkin (Cucurbita L.) has long been recognized not only as a nutritional food source but also as a plant of significant medicinal value. This article explores the multifaceted importance of pumpkin in both modern medicine and traditional folk healing practices. Rich in bioactive compounds such as carotenoids, tocopherols, flavonoids, and essential fatty acids, pumpkin exhibits a range of therapeutic properties including antioxidant, anti-inflammatory, antimicrobial, and antidiabetic effects. Clinical studies and ethnobotanical records reveal its use in managing conditions such as diabetes mellitus, hypertension, intestinal parasites, and prostate disorders. Moreover, pumpkin seed oil has gained prominence in urology and dermatology due to its beneficial impact on benign prostatic hyperplasia and skin regeneration. In folk medicine, various cultures have utilized different parts of the pumpkin—seeds, pulp, and peel—for healing wounds, boosting immunity, and improving digestion. This article presents a comprehensive review of recent scientific findings and historical applications, emphasizing the plant’s role as a bridge between natural remedies and evidence-based medical interventions.
Keywords: Cucurbita L; pumpkin; medicinal plants; folk medicine